Peningkatan Proses Berpikir Kritis Siswa Sekolah Dasar dengan Pembelajaran Berbasis Masalah - Endang Sri Maruti; Meleninda Cantika Widuri (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2023)
Critical thinking skills are very useful for solving problems and choosing the right decisions. One of the learning models that can be used to improve critical thinking skills is the problem-based learning model. The purpose of this study was to describe the increase in critical thinking skills possessed by elementary school students using a problem-based learning model in fourth grade students at SDN 02 Mojorejo. This research is a classroom action research that is realized in two skiluses. Data collection was carried out by observation, documentation and tests. Data analysis was performed with descriptive qualitative. The results of the study show that students' critical thinking skills can increase after the application of the problem-based learning model which is carried out during the second cycle.